Periorbital burns – A 6 year review of management and outcome. Issue 3 (May 2015) - Fitzgerald O'Connor, Edmund; Frew, Q.; Din, A.; Pleat, J.; Ashraff, S.; Ghazi-Nouri, S.; El-Muttardi, N.; Philp, B.; Dziewulski, P.
Highlights Facial burns are common. Early appreciation of an ocular injury is vital. The goal of surgery is to allow complete eye closure and to prevent lagophthalmos at rest. In our cohort of 103 patients over 6 years 4.8% developed late eye complications and 1% of patients lost vision in one eye.